Pengaruh Latihan Passing Berpasangan terhadap Kemampuan Passing Bawah Pemain Voli SMK Negeri 1 Bengkulu Selatan - Hayadi, Supian; Putra, Dwingki Marta; Apriansyah, Dolly (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
The purpose of this study were: To determine the effect of Paired Training on Lower Passing Ability of SMK Negeri 1 Bengkulu Selatan. This type of research is experimental research. The sample in this study were all volleyball players of SMK Negeri 1 Bengkulu Selatan totalling 15 people. The results of testing the hypothesis that the overall group obtained the initial test value mean 8.67 standard deviation 2.47, minimum value 5, and maximum value 15, and the final test mean 12.07, standard deviation 3.58, minimum value 7, and maximum value 19. Based on the measurement of the initial test and the final test using the t-test statistical approach of the overall training method group t count = 6.538 and t table (α = 0.05) = 1.761 which means t count> t table, so it can be concluded that there is a significant influence between paired passing exercises on the lower passing ability of volleyball players SMK Negeri 1 Bengkulu Selatan. As stated in the previous theoretical study, paired passing exercises are effective in improving the ability to pass down volleyball games.